The new city a novel - Amidon, Stephen 1959- (Doubleday, 2000)
A racial utopia disintegrates into conflict in this social satire. It happens in a planned community in Maryland which was designed to avoid economic disparity and racial tension. Everything works until a black tries to unseat a white in an election for city manager.
Keywords: Fathers and sons -- Fiction; Planned communities -- Maryland -- Fiction; Maryland -- Fiction; Fiktionale Darstellung; Domestic fiction